2014
DOI: 10.1039/c3cc49831j
|View full text |Cite
|
Sign up to set email alerts
|

A phthalocyanine–subphthalocyanine heterodinuclear dimer: comparison of spectroscopic properties with those of homodinuclear dimers of constituting units

Abstract: A phthalocyanine-subphthalocyanine heterodinuclear dimer has been disclosed for the first time with its unique flat-bowl-shaped structure revealed by X-ray crystallography. Its spectroscopic properties were compared with those of homodinuclear dimers of constituting units, as well as those of constituting monomeric units.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
18
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 22 publications
1
18
0
Order By: Relevance
“…TheT DDFT calculations estimated that the Qbands mainly consist of transitions between the six frontier molecular orbitals (MOs), the HOMO-1 and HOMO,a nd the LUMO-LUMO + 3, which are ascribed to products of linear combinations of the HOMO and the LUMO and LUMO + 1o fM1 (Figure 4; see also Table S1 in the Supporting Information). In the case of the homo-and heterodimer systems of Pc, SubPc, and related analogues sharing p-conjugated aromatic rings,s uch as benzene,n aphthalene,a nd anthracene, [19][20][21][22][23][24] the frontier MOs are known to be similarly developed by linear combination of the frontier MOs of the corresponding monomer species.I nt his respect, the through-space expansion of the conjugated systems through the cyclophane bridge in the case of the current SubPc dimer species was supported in theory. In fact, acertain amount of the MO coefficient was observed between the benzene rings of the cyclophane unit for the LUMO + 1o fCC and the LUMO of CV and VV (see Figures S3-S5).…”
Section: Methodsmentioning
confidence: 99%
“…TheT DDFT calculations estimated that the Qbands mainly consist of transitions between the six frontier molecular orbitals (MOs), the HOMO-1 and HOMO,a nd the LUMO-LUMO + 3, which are ascribed to products of linear combinations of the HOMO and the LUMO and LUMO + 1o fM1 (Figure 4; see also Table S1 in the Supporting Information). In the case of the homo-and heterodimer systems of Pc, SubPc, and related analogues sharing p-conjugated aromatic rings,s uch as benzene,n aphthalene,a nd anthracene, [19][20][21][22][23][24] the frontier MOs are known to be similarly developed by linear combination of the frontier MOs of the corresponding monomer species.I nt his respect, the through-space expansion of the conjugated systems through the cyclophane bridge in the case of the current SubPc dimer species was supported in theory. In fact, acertain amount of the MO coefficient was observed between the benzene rings of the cyclophane unit for the LUMO + 1o fCC and the LUMO of CV and VV (see Figures S3-S5).…”
Section: Methodsmentioning
confidence: 99%
“…[3, 5a] The fully trifluoroethoxy-coated Pc-SubPc heterodinuclear dimer 2 has au nique combination of af lat Pc structure and ab owl-shaped SubPc structure, as wasr evealed by X-ray crystallography in 2014( Figure 1b). [6] Interestingly, we found that toluene was attracted to the concave p-surface of the SubPc moiety of 2.F ollowing the X-ray crystallographic analysiso f2,w eh ave been interested in the potentialo f SubPc/arene clathrates. The concave p-surface space in SubPcs should be useful for trapping small arene compounds and the resultingc lathrates should be suitable for X-ray crystallographic analysis.…”
mentioning
confidence: 99%
“…We found that dispersion interactions are the major impetusf or clathrate formation while the contributions of fluorinee ffects and electrostatic interactions to the attraction are not large. Since trifluoroethoxy-coated SubPcs are stable and easy to synthesize andh andle, [3,5,6] they may serve as at ool for the crystallization of small, noncrystalline aromatic compounds in the form of trifluoroethoxy-coated SubPc/arene clathrates (Figure 1c).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The TDDFT calculations estimated that the Q bands mainly consist of transitions between the six frontier molecular orbitals (MOs), the HOMO-1 and HOMO, and the LUMO-LUMO + 3, which are ascribed to products of linear combinations of the HOMO and the LUMO and LUMO + 1 of M1 (Figure 4; see also Table S1 in the Supporting Information). In the case of the homo-and heterodimer systems of Pc, SubPc, and related analogues sharing p-conjugated aromatic rings, such as benzene, naphthalene, and anthracene, [19][20][21][22][23][24] the frontier MOs are known to be similarly developed by linear combination of the frontier MOs of the corresponding monomer species. In this respect, the through-space expansion of the conjugated systems through the cyclophane bridge in the case of the current SubPc dimer species was supported in theory.…”
mentioning
confidence: 99%